Addictive Cell Phone Usage: the Relationship between Impulsiveness and Behavioral Addiction - Maryam Siddiqui, Amena Zehra Ali (Pakistan Journal of Psychology, 2015)
The present study was designed to investigate the predictive relationship between impulsiveness and behavioral addiction. The sample of the study comprised of 100 male and female with an age range of 14-40. Mobile Phone Involvement Questionnaire (Walsh, White, & Young, 2010) which is based on Brown’s (1993,1997) Behavioral Addiction Components was used to measure behavioral addiction as manifested by addictive cell phone usage. To measure personality trait of impulsiveness, Barratt Impulsiveness Scale (Patton, Stanford, & Barratt, 1995) was administered. Linear Regression Analysis was applied to interpret the data in statistical terminology. The results indicated impulsiveness and it’s all three facets: attentional impuslivesnes, motor impulsiveness and non-planning impulsiveness to be the significant predictors of behavioral addiction as manifested by cell phone usage. The findings have implications for researchers and clinicians.